Mechanical and Wear Properties of Acrylonitrile Butadiene Styrene Polymer Composites - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2013)
In the present work, acrylonitrile butadiene styrene based composites filled with aluminum, boron carbide and glass spheres particles were prepared. Fillers contents in the ABS were 5, 10, 15, and 20 wt%. The mechanical and wear properties of the polymer composites were investigated. The structural properties of the composites are characterized using a scanning electron microscopy.
Keywords: Acrylonitrile Butadiene Styrene; wear; friction; mechanical properties; talc; FRICTION; BEHAVIOR